Kajian Strategi Restrukturisasi Kredit Usaha Rakyat dalam Mengatasi Loan At Risk (LAR) (Coopetition : Jurnal Ilmiah Manajemen, 2024)
The problem that is often faced by the banking world in general is the problem of problematic credit. The same thing happened to Bank BRI. The consequences of these problematic loans can increase the NPL level which will impact the bank's health if not handled quickly and appropriately. So in this case the bank uses credit restructuring by referring to the Loan At Risk (LAR) financial ratio as a restructuring strategy. The same thing happened to Bank BRI, where the factor that led to the implementation of the restructuring policy was because in 2019 the Covid-19 pandemic occurred which resulted in many customers being affected and unable to repay their credit on time. The consequences of these problematic loans can increase the NPL level which will impact the bank's health if not handled quickly and appropriately. So in this case the bank uses credit restructuring as a strategy to reduce non-performing loans. This type of research is qualitative descriptive analysis. Research data was collected using interviews, observation, documentation, and questionnaires. The benefits of research can be used to develop knowledge in the field of financial institutions, especially regarding the implementation of restructuring strategies in overcoming Loan At Risk (LAR). From the implementation of credit restructuring carried out by BRI Bank, it can be concluded that the implementation of credit restructuring as a strategy for reducing problem loans has been carried out effectively in accordance with the procedures and policies that have been determined by the bank's internal and banking regulations. This effectiveness can be proven by the decreasing percentage of LAR levels every year.